2002
DOI: 10.1021/ie010676i
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Size in a Cocurrent Fiber Slurry

Abstract: Bubble diameter measurements in a two-dimensional cocurrent bubble column are obtained using a gas−liquid−solid system in which the solid component is a cellulose fiber. Flash X-ray radiography, a noninvasive measurement technique, is used to record bubble size in the opaque slurry at various operating conditions. Results are presented for a range of fiber mass fractions (0 ≤ C ≤ 1.5%), a range of superficial gas velocities (1 ≤ υg ≤ 4 cm/s), two superficial liquid velocities (υl = 1 or 2 cm/s), and two column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…During their rise, bubbles have to push solids away from their path. In addition, fibres in model suspensions dampen the flow velocity fluctuations and resist the flow from becoming turbulent, as reported in [3,4,12]. In process waters, bubbles were seen to align in swarms more strongly than in pure gasliquid suspension.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…During their rise, bubbles have to push solids away from their path. In addition, fibres in model suspensions dampen the flow velocity fluctuations and resist the flow from becoming turbulent, as reported in [3,4,12]. In process waters, bubbles were seen to align in swarms more strongly than in pure gasliquid suspension.…”
Section: Resultsmentioning
confidence: 65%
“…Fibre content appears to have even higher impact on mean bubble size than changes in surface tension and viscosity. Although increased fibre consistency is also noted to promote large bubble formation [3,4], that trend is not visible here. Actually fewer micro-bubbles are generated in fibre suspensions than in pure liquids.…”
Section: Micro-bubble Size Distribution In Tested Suspensionsmentioning
confidence: 65%
See 1 more Smart Citation
“…The presence of fibers can make the effective rheological properties of a fiber suspension significantly different from those of the suspending fluid [64][65][66]. Fiber floes or networks can significantly affect bubble motion, coalescence, and breakup, and thus, gas holdup in the bubble column [2,5,11,12,20,[67][68][69]. Pelton and Piette [69] reported that the main reason bubbles are held up in a fiber suspension is mechanical confinement, not bubble adhesion to fibers.…”
Section: Fiber Physical Propertiesmentioning
confidence: 99%
“…Bubble size distribution in gas-liquid-fiber flows and its variation with fiber mass fraction and fiber type have been investigated in semi-batch [8-1 0] and cocurrent bubble columns [11 ]. Gas holdup in gas-liquid-fiber systems has also been studied in both semi-batch [2,[12][13][14][15][16][17][18] and co current [2,[19][20][21][22][23] bubble columns.…”
Section: Introductionmentioning
confidence: 99%